2015
DOI: 10.1051/0004-6361/201323284
|View full text |Cite
|
Sign up to set email alerts
|

Supergranular-scale magnetic flux emergence beneath an unstable filament

Abstract: Aims. Here we report evidence of a large solar filament eruption on 2013, September 29. This smooth eruption, which passed without any previous flare, formed after a two-ribbon flare and a coronal mass ejection towards Earth. The coronal mass ejection generated a moderate geomagnetic storm on 2013, October 2 with very serious localized effects. The whole event passed unnoticed to flarewarning systems. Methods. We have conducted multi-wavelength analyses of the Solar Dynamics Observatory through Atmospheric Ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
4
1
Order By: Relevance
“…Related to this, the spatial size and duration of the heating caused by internal reconnection within the trigger field represented by precursor brightenings is different among the events. In addition, empirically from this and other studies (Bamba et al 2013(Bamba et al , 2014Palacios et al 2015;Bamba et al 2017a,b;Wang et al 2017;Woods et al 2017), the duration varies from several hours to a few seconds and the spatial size were from a few to dozens of arcseconds.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Related to this, the spatial size and duration of the heating caused by internal reconnection within the trigger field represented by precursor brightenings is different among the events. In addition, empirically from this and other studies (Bamba et al 2013(Bamba et al , 2014Palacios et al 2015;Bamba et al 2017a,b;Wang et al 2017;Woods et al 2017), the duration varies from several hours to a few seconds and the spatial size were from a few to dozens of arcseconds.…”
Section: Resultssupporting
confidence: 63%
“…Another interesting topic for discussion is the result that the OP type events were rare compared to the RS types, at least in this study. Some other studies found events which were suggested to be triggered by the OP type small magnetic structure (Palacios et al 2015;Wang et al 2017;Woods et al 2017). However, so far we found only two OP type flare events (already shown by Bamba et al (2013) by the same method of this study) whereas six events were classified as the RS type in this study.…”
Section: Difference Of the Incidence Rate Of Op And Rs Typescontrasting
confidence: 50%
“…For many hot channel eruption events, their exact origin and initiation process still remain heated debated yet. Some observation supported that before the hot channel eruption, a corresponding MFR may already exist (e.g., Liu et al 2016;Wang et al 2016;) and slow photospheric flows might be important for its gradual formation (e.g., Yan et al 2018;Hou et al 2018;Vasantharaju et al 2019); while others argued that they can also be newly built up via rapid coronal reconnection during the eruption (Cheng et al 2011;Song et al 2014;Palacios et al 2015). For their loss-of-equilibrium, some researchers found that the loss-of-equilibrium of hot channel is initially facilitated by the breakout type (e.g., Chen et al 2016;Mitra et al 2018) or tether-cutting type (e.g., Chen et al 2014;Joshi et al 2015;Dudík et al 2016;Chen et al 2018) pre-flare reconnection, but others believed the loss-ofequilibrium of hot channel may be directly triggered the ideal MHD instabilities (e.g., Liu et al 2007;Bi et al 2015;Vemareddy et al 2017).…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Thereinto, the latter two, jointly termed as the main phase, correspond to the impulsive acceleration of the erupting CME flux-rope, while the less-studied precursor phase includes key information on the eruptive structure and its trigger process. In the past, the limited observations showed that precursor activities of solar eruptions can come in various forms, in which preceding flux emergence (e.g., Palacios et al 2015;Yan et al 2017;Yang, & Chen 2019) or cancellation (e.g., Green et al 2011;Yang et al 2016;Chen et al 2018) in magnetograms, pre-eruption brightenings in H α /EUV images (e.g., Bi et al 2012;Dudík et al 2016;Wang et al 2017;Awasthi et al 2018;Chen et al 2018), as well as non-thermal processes in microwave or hard X-ray wavelength (Joshi et al 2011;Altyntsev et al 2012;Chen et al 2016) are most common ones. In recent years, in the precursor phase of many CME/flare eruptive events, a type of new progenitors of CME flux-ropes, namely hot channels (HCs, Cheng et al 2011;Zhang et al 2012;Cheng et al 2013), have been detected in the AIA high-temperature passbands (e.g., 131 and 94 Å).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed description on the physics of flux emergence may be found in Cheung and Isobe (2014). The flux emergence associated with filament eruptions can either be located directly beneath the flux rope, as described by Palacios et al (2015), or to the side. Emergence beneath the flux rope can trigger the eruption through tether-cutting, as described by Moore et al (2001).…”
Section: Introductionmentioning
confidence: 99%